Olfactory response of red palm weevil, Rhynchophorous ferrugineus (Olivier) (Coleoptera: Dryophthoridae), to host / food volatiles - Venugopal, Vibina; Subaharan, Kesavan (Journal of Plantation Crops, 2019)
Red palm weevil, Rhynchophorus ferrugineus (Olivier), is a destructive pest of palms across the globe. Concealed nature of the pest is a hurdle in its management. Pheromone traps are a vital component in integrated management of the pest. Previous experiences reveal that use of pheromone, in isolation, trapped lower number of weevils as compared to their use in tandem with food baits. Attempts were made to study physiological and behavioral response of RPW to food baits viz., banana, pineapple and coconut petiole. Electrophysiological responses revealed that head space volatiles trapped from banana elicited the highest EAG response of 0.7 mV followed by pineapple (0.65 mV) and coconut petiole (0.2 mV). Behaviourally, orientation of adult weevils to banana, pineapple and coconut petiole volatiles ranged from 70 to 75 per cent. In field assay, banana volatiles compounds with aggregation pheromone attracted a higher mean number of adult weevils of 55.3, followed by 51.7 with pineapple and 40.6 with coconut petiole volatiles.